Overview Leptospirosis in Agricultural: Literature Review - Alfid Tri Afandi; Enggal Hadi Kurniyawan; Putri Nabilah; Ira Purba Wanda; Fatikah Rizki Arum Mauliya; Dicky Endrian Kurniawan; Kholid Rosyidi Muhammad Nur (KHD Production, 2023)
The spread of leptospirosis worldwide shows a high incidence rate. The disease is transmitted through the urine of animals infected with leptospira bacteria. Factors that can affect the incidence of leptospirosis are gender, age, uncovered food storage, the presence of rats, the presence of pets and contact with standing water. The writing method used is literature review. The literature search used Google Scholar, PubMed, and ScienceDirect databases with the period 2019-2023. The results of a review of 10 national and international journal articles show that leptospirosis has considerable potential for farmers because the spread occurs directly through blood or urine containing germs into the human body, and indirect transmission can occur through stagnant water, rivers, lakes, drains, and mud contaminated by animal urine. The harmful effects of spreading leptospirosis in an agricultural environment can lead to infection in humans and livestock. Early symptoms in humans include fever, headache, and nausea. If not treated promptly, the disease can progress to a more serious and potentially life-threatening condition. Therefore, the role of nurses in monitoring the health of farm animals and educating farmers on preventive measures is crucial in maintaining animal health and keeping the agricultural sector sustainable.